أثر تطبيق الحمض الأميني "سيستين" رشاً على ارتفاع صنف القطن حلب 33-1 وبعض مكونات الغلة - عبد العزيز, محمد; خلاصي, حسام الدين; علي, عزام (Latakia University Journal -Biological Sciences Series, 2019)
نفّذ البحث في موسم 2016 في منطقة الغاب لدراسة تأثير ثلاث معدلات للرش بالحمض الأميني السيستين (1500-1000-500 ppm) على نمو وصفات التبكير والغلة لصنف القطن حلب 33-1 ومقارنة النتائج مع نباتات الشاهد بدون إضافة. تم رش الحمض الأميني في بداية مرحلة الإزهار، تم أخذ القراءات وحساب المتوسطات إذ بلغت قيم ارتفاع النبات (84.40، 86.46، 89.38، 89.80 سم)، وعدد الفروع الثمرية (11.31، 12.78، 13.69، 14.43 فرع)، وعدد الجوزات الكلية (17.04،17.87، 18.06، 18.18 جوزة)، وعدد الجوزات المتفتحة (12.91، 13.22، 15.44، 16.26 جوزة)، ووزن الجوزة الواحدة (4.96، 5.11، 5.43، 5.49 غ)، وغلة القطن المحبوب (3945، 4220، 5205، 5543 كغ/هـ)، ودليل البذور(10.47، 10.68، 11.98، 12.03 غ) لنباتات الشاهد والمعدلات المستخدمة 500، 1000 و 1500 بالترتيب. أظهر التحليل الإحصائي أن المعدل 1500 ppm أعطى أفضل النتائج في جميع الصفات المدروسة وكانت الفروق معنوية في صفات عدد الفروع الثمرية، عدد الجوزات الكلية، عدد الجوزات المتفتحة وغلة القطن المحبوب. لم تظهر فروق معنوية بين المعدلين 1500 ppm و 1000 ppm في صفة ارتفاع النبات ، وزن جوزة واحدة و دليل البذور. كذلك لم تظهر فروق معنوية بين المعدل 500 ppm والشاهد في صفة عدد الجوزات المتفتحة ، وزن جوزة واحدة و دليل البذور. The research was carried out during 2016 in Al-Ghab area to study the effect of three rates of amino acid (500,1000 and 1500 ppm) on growth and yield component of Variety (Allepo 33-1) and compare The results with Control plants. The Amino Acid was sprayed at the flowering, results were taken and the averages were calculated. Plant height was (84.40, 86.46, 89.38, 89.80 cm), Sympodial Branches Number was (11.31, 12.78, 13.69, 14.43), Total Bolls Number was (17.04, 17.87, 18.06, 18.18 ball), Opened Bolls Number was (12.91, 13.22, 15.44, 16.26 ball), Boll Weight was (4.96, 5.11, 5.43, 5.49 g) , cotton seed yield was (3945, 4220, 5206, 5543 kg. h-1), seed index was (10.47, 10.68, 11.98, 12.03, 12.03 g) for Control plants and amino acid rates (500,1000 and 1500 ppm) respectively. Statistical analysis showed that the best results in all studied characters were at the rate (1500 ppm). There were significant differences between plants in number of fruiting branches, number of total and opened balls, seed index characters. There were no significant differences between the rate (1000ppm and 1500ppm) plants in Plant height, weight of ball and seed index characters. There were no significant differences between the rate (500ppm) and the control plants in number of opened balls, weight of ball and seed index characters.